Built environments and frailty in older adults: A three-year longitudinal JAGES study. (November 2022) - Mori, Yuta; Tsuji, Taishi; Watanabe, Ryota; Hanazato, Masamichi; Miyazawa, Takuto; Kondo, Katsunori
Highlight: This study investigated the relationship between built environments and the onset of frailty after 3 years. Individual-level frailty risk was high in four negative built environment types and low in four positive types . However, at the community level, older adults living in areas with 10% more locations that were difficult for walking had a 3% lower risk of developing frailty at 3 years, even after we adjusted for individual levels. It is necessary to plan the desired built environment for frail prevention. Abstract: Background: This study investigated the relationship between built environments and the onset of frailty after 3 years. Methods: This was a longitudinal study using prospective cohort data from the 2013 Japan Gerontological Evaluation Study on 38, 829 older adults nested in 562 comunnities who were not frail. The dependent variable, frailty, was assessed using the Kihon checklist. The explanatory variables were eight items for the built environment at the individual and community levels. To consider each level of built environment simultaneously, multilevel Poisson regression analysis was used to calculate risk ratios and 95% confidence intervals. Results: After 3 years of follow-up, the onset of frailty was 2740 (7.1%) in 2016. At the individual level, there was an increased risk of developing frailty in negative built environments, such as locations with graffiti or garbage (incidence rate ratio (IRR), 1.15; confidence interval (CI), 1.05–1.25). Positive built environments, such as areas with access to parks and sidewalks (IRR, 0.78; CI, 0.70–0.88), lowered the risk of developing frailty. At the community level, the risk of developing frailty was lower only in areas with locations difficult for walking (hills or steps) (IRR, 0.97; CI, 0.94–0.99). Conclusions: At the individual level, frailty onset was associated with all built environments. However, irrespective of their answers, there was a lower risk of developing frailty among older adults living in areas where walking was difficult. It would be desirable to verify whether the risk of developing frailty can be reduced by changing the built environment.